High occurrence of antihistamine resistance in patients with recurrent idiopathic angioedema. Issue 1 (12th July 2019) - Hofman, Zonne L. M.; van West, Nikki; Hack, C. Erik; Knulst, André C.; Maas, Coen; Röckmann, Heike
Abstract: Antihistamines are the most prescribed therapy in recurrent idiopathic angioedema, yet little is known about their efficacy. Herein, we report on clinical improvement with antihistamine therapy in 120 patients evaluating angioedema attack frequency. A high incidence (36%) of antihistamine refractory cases was observed. Forty percent of patients on antihistamine prophylaxis suffered from 1 or more angioedema attacks per month. Our findings stress the need for additional treatment options for recurrent idiopathic angioedema.